(4y+8)-(4+3y)=8

Simple and best practice solution for (4y+8)-(4+3y)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4y+8)-(4+3y)=8 equation:


Simplifying
(4y + 8) + -1(4 + 3y) = 8

Reorder the terms:
(8 + 4y) + -1(4 + 3y) = 8

Remove parenthesis around (8 + 4y)
8 + 4y + -1(4 + 3y) = 8
8 + 4y + (4 * -1 + 3y * -1) = 8
8 + 4y + (-4 + -3y) = 8

Reorder the terms:
8 + -4 + 4y + -3y = 8

Combine like terms: 8 + -4 = 4
4 + 4y + -3y = 8

Combine like terms: 4y + -3y = 1y
4 + 1y = 8

Solving
4 + 1y = 8

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 1y = 8 + -4

Combine like terms: 4 + -4 = 0
0 + 1y = 8 + -4
1y = 8 + -4

Combine like terms: 8 + -4 = 4
1y = 4

Divide each side by '1'.
y = 4

Simplifying
y = 4

See similar equations:

| 4x^2-10x+7=0 | | 6a^2-3a+a-2a^2= | | 9y+27=-72 | | -x/2+3=-12 | | 92=6(r+2)+4r | | 3y-1/2=z | | 90=6(3x+1)-6x | | 5x-12+3x+6=72 | | -40+8=-10+-24 | | 4x^6-3y^4+6x^6+6y^4= | | -2=5+1x | | x/3-9=10 | | 2t+3+3t-4t=4+2 | | 4x^6-3y^4+6x^6y^4-6x^6+6y^4= | | -x-2=6 | | x/2-13=11 | | -53+29=x | | x^2+16=-5 | | -53+23=x | | -53+=x | | 5x^2+5y^2=25 | | a=36-cforb | | 3x+12=-18x-9x+1 | | -53+29= | | 5.35=2.37 | | -2+8=-20 | | 2x+14=15x-10 | | 4.8x-3=3.8 | | 3/x+2=6/x-5 | | -2=14 | | 4(x-3)+y=21 | | 9z+12=9-3z |

Equations solver categories